Differential Diagnosis of Calvarial Tumors: A Series of 8 Cases - Jitesh Kumar Sharma; Rashim Kataria; Madhur Choudhary; Devendra Kumar Purohit (Indian Journal of Neurosurgery)
Introduction To present and discuss the clinical presentations, investigations, and treatment options for skull bone tumors. Materials and Methods This study was conducted from January 2019 to December 2019 at the Department of Neurosurgery. During this period, eight patients presented with skull bone tumor in the outpatient department. All patients were thoroughly investigated. Surgery was conducted on six patients and two patients had disseminated carcinoma; hence, surgery was not done. Patients were regularly followed-up after the surgery. Results In our study, out of eight cases, five were females and three were males. We had two cases of fibrous dysplasia, two cases of osteomas, and one case each of brown tumor, metastases from lung carcinoma, metastases from follicular carcinoma of thyroid, and Ewing sarcoma/primitive neuroectodermal tumor (PNET). Excision of tumor was performed where indicated and adjuvant chemo- and radiotherapy was suggested wherever required. Conclusion Bony tumors of the skull are uncommon diseases for the neurosurgeons. These tumors require a careful diagnosis with suitable radiological examinations and proper clinical correlation for proper management.